Use the remainder theorem!

Algebra Level 2

Given that x 2 5 x + 4 x^{ 2 }-5x+4 is a factor of the expression 2 x 4 + h x 3 + k x 2 + 34 x 24 2{ x }^{ 4 }+hx^{ 3 }+kx^{ 2 }+34x-24 . What is the factorized form of the expression?

Hint: Find the values of h h and k k first.

( x 1 ) ( x 4 ) ( x 3 ) ( 3 x 2 ) (x-1)(x-4)(x-3)(3x-2) ( x 1 ) ( x 4 ) ( 3 x 2 ) ( x + 2 ) (x-1)(x-4)(3x-2)(x+2) ( x 1 ) ( x 4 ) ( 2 x 3 ) ( 3 x 2 ) (x-1)(x-4)(2x-3)(3x-2) ( x 1 ) ( x 4 ) ( 2 x 3 ) ( x + 2 ) (x-1)(x-4)(2x-3)(x+2)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Let f ( x ) = 2 x 4 + h x 3 + k x 2 + 34 x 24 f(x) = 2x^4+hx^3+kx^2+34x-24 . Since x 2 5 x + 4 = ( x 1 ) ( x 4 ) x^2-5x+4=(x-1)(x-4) , This implies that:

{ f ( 1 ) = 2 + h + k + 34 24 = 0 h + k = 12 . . . ( 1 ) f ( 4 ) = 512 + 64 h + 16 h + 136 24 = 0 4 h + k = 39 . . . ( 2 ) \begin{cases} f(1) = 2+h+k+34-24 =0 & \implies h+k = -12 &...(1) \\ f(4) = 512 + 64h + 16h + 136-24 = 0 & \implies 4h +k = -39 &...(2) \end{cases}

( 2 ) ( 1 ) : 3 h = 27 h = 9 ( 1 ) : k = 3 \begin{aligned} (2)-(1): \quad 3h & = -27 \\ \implies h & = -9 \\ (1): \quad \implies k & = -3 \end{aligned}

f ( x ) = 2 x 4 9 x 3 3 x 2 + 34 x 24 = ( x 2 5 x + 4 ) ( 2 x 2 + x 6 ) = ( x 1 ) ( x 4 ) ( 2 x 3 ) ( x + 2 ) \begin{aligned} \implies f(x) & = 2x^4-9x^3-3x^2+34x-24 \\ & = (x^2-5x+4)(2x^2+x-6) \\ & = \boxed{(x-1)(x-4)(2x-3)(x+2)} \end{aligned}

Great solution, sir.

Armain Labeeb - 4 years, 11 months ago
Akash Shukla
Jul 5, 2016

If we look at the option, then the coefficient of x 4 ( 2 ) x^4-(2) could be get in option 4 only.As in other option we would get 3 , 6 , 3 3,6,3 as a coefficient of x 4 x^4

That's what I did.. The options were very poorly framed.

Rishabh Jain - 4 years, 11 months ago
Hung Woei Neoh
Jul 5, 2016

A solution that doesn't require you to find the values of h h and k k :

Since x 2 5 x + 4 x^2-5x+4 is a factor of the expression, we can say that

( x 2 5 x + 4 ) ( a x 2 + b x + c ) = 2 x 4 + h x 3 + k x 2 + 34 x 24 (x^2-5x+4)(ax^2+bx+c) = 2x^4+hx^3+kx^2+34x-24

for some constants a , b a,\;b and c c . Expand the left hand side:

a x 4 + ( b 5 a ) x 3 + ( 4 a 5 b + c ) x 2 + ( 4 b 5 c ) x + 4 c = 2 x 4 + h x 3 + k x 2 + 34 x 24 ax^4+(b-5a)x^3+(4a-5b+c)x^2+(4b-5c)x+4c=2x^4+hx^3+kx^2+34x-24

Compare the terms of the expressions:

a x 4 = 2 x 4 a = 2 4 c = 24 c = 6 ( 4 b 5 ( 6 ) ) x = 34 x 4 b + 30 = 34 4 b = 4 b = 1 ax^4=2x^4 \implies a=2\\ 4c=-24 \implies c=-6\\ \big(4b-5(-6)\big)x=34x\\ 4b+30=34\\ 4b=4 \implies b=1

Therefore,

2 x 4 + h x 3 + k x 2 + 34 x 24 = ( x 2 5 x + 4 ) ( 2 x 2 + x 6 ) = ( x 1 ) ( x 4 ) ( 2 x 3 ) ( x + 2 ) 2x^4+hx^3+kx^2+34x-24\\ =(x^2-5x+4)(2x^2+x-6)\\ =\boxed{(x-1)(x-4)(2x-3)(x+2)}

Armain Labeeb
Jul 4, 2016

Let f ( x ) = 2 x 4 + h x 3 + k x 2 + 34 x 24 f\left( x \right) =2{ x }^{ 4 }{ +hx }^{ 3 }+k{ x }^{ 2 }+34x-24 .

We know,

x 2 5 x + 4 = ( x 1 ) ( x 4 ) x^{ 2 }-5x+4=(x-1)(x-4)

Since x 2 5 x + 4 x^{ 2 }-5x+4 is a factor of f ( x ) f\left( x \right) , it follows that ( x 1 ) (x-1) and ( x 4 ) (x-4) are factors of f ( x ) f\left( x \right) .

Thus,

f ( 1 ) = 0 a n d f ( 4 ) = 0 f\left( 1 \right) =0\quad and\quad f\left( 4 \right) =0 .

f ( 1 ) = 2 ( 1 ) 4 + h ( 1 ) 3 + k ( 1 ) 2 + 34 ( 1 ) 24 = 0 ( 1 ) f ( 4 ) = 2 ( 4 ) 4 + h ( 4 ) 3 + k ( 4 ) 2 + 34 ( 4 ) 24 = 0 ( 2 ) f\left( 1 \right) =2(1)^{ 4 }+h(1)^{ 3 }+k(1)^{ 2 }+34(1)-24=0\quad \quad \quad \longrightarrow (1)\\ f\left( 4 \right) =2(4)^{ 4 }+h(4)^{ 3 }+k(4)^{ 2 }+34(4)-24=0\quad \quad \quad \longrightarrow (2)

From ( 1 ) : h + k = 12 = 0 ( 3 ) (1):\quad \quad \quad \quad \quad h+k=12=0 \quad \quad\longrightarrow (3)

From ( 2 ) : 64 h + 16 k + 624 = 0 (2):\quad \quad \quad 64h+16k+624=0

i.e., 4 h + k + 39 = 0 ( 4 ) \quad \quad \quad \quad \quad \quad \quad 4h+k+39=0 \quad \quad \longrightarrow (4)

Solving ( 3 ) (3) and ( 4 ) (4) simultaneously we have, h = 9 h=-9 and k = 3 k=-3 .

Now,

f ( x ) = 2 x 4 9 x 3 3 x 2 + 34 x 24 f\left( x \right) =2{ x }^{ 4 }{ -9x }^{ 3 }-3{ x }^{ 2 }+34x-24

By long division, we have:

2 x 2 + x 6 x 2 5 x + 4 ) 2 x 4 9 x 3 3 x 2 + 34 x 24 2 x 4 10 x 3 + 8 x 2 x 3 11 x 2 + 34 x x 3 5 x 2 + 4 x 6 x 2 + 30 x 24 6 x 2 + 30 x 24 0 \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad 2x^{ 2 }\quad +\quad x\quad -\quad 6\quad \quad \\ x^{ 2 }\quad -5x\quad +4)\overline { 2{ x }^{ 4 }{ \quad -9x }^{ 3 }\quad -3{ x }^{ 2 }\quad +34x\quad -24 } \\ \quad \quad \quad \quad \quad \quad \quad \underline { 2{ x }^{ 4 }\quad{ -10x }^{ 3 }\quad +8{ x }^{ 2 }\quad \quad \quad \quad \quad \quad \quad } \\ \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad { \quad x }^{ 3 }\quad -11{ x }^{ 2 }\quad +34x\\ \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \underline { { x }^{ 3 }\quad -\quad 5{ x }^{ 2 } +\quad 4x\quad \quad \quad \quad } \\ \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad -\quad 6x^{ 2 }\quad +30x\quad -24\\ \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \underline { -\quad 6x^{ 2 }\quad +30x\quad -24 } \\ \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad \quad0

f ( x ) = ( x 2 5 x + 4 ) ( 2 x 2 + x 6 ) = ( x 1 ) ( x 4 ) ( 2 x 3 ) ( x + 2 ) \therefore f\left( x \right) =(x^{ 2 }-5x+4)(2x^{ 2 }+x-6)\\ \quad \quad \quad =\boxed{(x-1)(x-4)(2x-3)(x+2)}

Hello, I would pretty much appreciate if you guys can teach me how to do long division in LaTex. In my solution, I had to use mnay "\quad" s to allign my text as i want and it still looks horrible. Help is appreciated.

Armain Labeeb - 4 years, 11 months ago

Log in to reply

You can use "\;" or "\," for shorter spacings

Hung Woei Neoh - 4 years, 11 months ago

Log in to reply

Thanks so much!!!!!

Armain Labeeb - 4 years, 11 months ago
Arinjay Singhal
Mar 25, 2019

Let x^2 - 5x + 4= f(a) = ( x - 1)(x - 4)
.We have to find the remaining 2 factors. .In the given expression the first term is 2x^4. .This 2x^4 is formed by product of x^2 of f(a) and the first term of remaining factor. .Hence,the first term of remaining factor is 2x^2. .By options we find that (2x - 3)(x + 2) gives 2x^2 as first term. .Hence : (x - 1)(x - 4)(2x - 3)(x + 2)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...